An Australian Perspective On Quality Outcomes of Inclusive Employment - Trevor Parmenter (Disability Studies Quarterly, 2002)
Work is an important activity in modern society. Most people spend a considerable part of their daily lives in working or training and preparing for work. Modern societies often put considerable resources into creating jobs and educating and training their citizens for paid employment. Changing conceptualizations about disability, the influence of normalization principles, advocacy, civil rights, international and national legislative initiatives, and most recently the self-determination movement have all recognized the important role of employment in the lives of people with disabilities. These have contributed significantly to the movement towards integrated, supported employment for this population. This paper will present the findings of two Australian studies that have examined the roles that employment play in the lives of people with disabilities. Implications for future research and policy directions will be indicated.